A computational software tool for the minimization of costs and greenhouse gas emissions associated with water distribution systems. (July 2015) - Stokes, Christopher S.; Simpson, Angus R.; Maier, Holger R.
Abstract: While evolutionary algorithms have been applied extensively to water resource problems, there remains a need to unify and consolidate computational and software approaches to solving these problems. In order to facilitate this for the minimization of costs and greenhouse gas emissions of water distribution systems, the water distribution cost-emissions nexus (WCEN) computational software framework is introduced in this paper. The software is freely available and can be easily modified in order to facilitate consistency of modeling, simulation and evaluation within different research studies. In addition, it enables consideration of the time-dependent variation of operational choices, such as emissions factors, electricity tariffs and water demands, which has not been done previously. The utility of the framework is demonstrated for a case study, the results of which show that consideration of such variations can significantly affect optimal design and operational decisions, as well as their costs and GHG emissions. Highlights: Computational software framework tool for use with water distribution systems. Minimization of capital and pumping operational costs and greenhouse gas emissions. Time dependency of emissions factors, water demands and electricity tariffs.